Collaborative Governance in Public Health Policy Implementation: A Literature Review in the Southeast Asia Region Including Indonesia - Arianny, Margaretha Porman; Adisasmito, Wiku (Devotion : Journal of Research and Community Service, 2024)
In the context of Indonesia, public health issues necessitate a comprehensive and coordinated strategy involving various stakeholders. Collaborative Governance serves as a means to materialize this approach. The purpose of this study is to identify instances of Collaborative Governance that have been implemented or are currently underway in public health improvement programs. research used a qualitative methodology, with data acquired through an exhaustive literature review. Data reduction, presentation, and conclusion form the three stages of data analysis. Findings from this literature review indicate that Collaborative Governance has been implemented in several public health programs in Indonesia. These programs involve stakeholders from both the government and non-governmental sectors, including communities, non-profit organizations, and industry associations. Collaborative Governance is achieved through regular meetings, coordination committees, and the use of digital platforms to facilitate information exchange and monitor program implementation. Successful examples of Collaborative Governance in public health programs in Indonesia include initiatives for infectious disease control, where the government collaborates with international organizations, pharmaceutical companies, and local communities to enhance health awareness.